La Musicoterapia para el desarrollo artístico de los niños del paralelo A, centro inicial San Rafael ubicado en el cantón Riobamba, provincia de Chimborazo. año lectivo 2017 – 2018. - Aguilera Aucancela, Henry Danilo (2018)
The objective of this research is to determine the influence of "music therapy on the artistic development of children from class "A", in “San Rafael” elementary school center. It is located in Riobamba canton, Chimborazo province, during schooling year 2017 - 2018 It has a number of 36 students in the Educational center. A non-experimental research was conducted, since none of the variables were manipulated. It was based on an observation, the subject was studied in order to identify the benefits of music therapy in the artistic development of children from early ages and; thus to draw out some conclusions and verify them. This type of research performed a descriptive method, field, bibliographic and analytical views that identified the characteristics of the studied reality. Before the investigated phenomenon some information was scrutinized to determine it causes and effects, including the information from the field. The studied elements were observed to determine what afflicts to the target students in the mentioned institution. The type of design is descriptive and allows describing variables; the performed technique was the observation since it captures directly the investigated object. Observation cards, as an instrument, allowed the study and interpretation of results. It concluded that music therapy is effective for children's artistic development, enhancing their abilities. Also, it contributes to their integral development, as children.